Improvements in acne and skin oiliness with tazarotene 0.045% lotion in patients with oily skin. (31st December 2023) - Tanghetti, Emil A.; Zeichner, Joshua A.; Gold, Michael; Sadick, Neil; Cook-Bolden, Fran E.; Kircik, Leon H.; Stein Gold, Linda; Weiss, Jonathan; Tyring, Stephen K.; Del Rosso, James Q.; Guenin, Eric
Abstract: Background: Excessive sebum production is a factor in acne development. Tazarotene 0.045% lotion has demonstrated reductions in acne lesions and acne-induced sequelae. Objective: Evaluate efficacy, changes in skin oiliness, and safety with tazarotene 0.045% lotion in participants with moderate-to-severe acne and oily skin. Methods: In two phase 3, double-blind, 12-week studies (NCT03168321; NCT03168334), participants aged ≥ 9 years with moderate-to-severe acne were randomized 1:1 to once-daily tazarotene 0.045% lotion or vehicle lotion ( N = 1614). This pooled, post hoc analysis included only participants self-categorized with oily skin at baseline on the Acne-Specific Quality of Life questionnaire item 19 (scores: 0 [extremely oily] to 6 [not at all oily]). Inflammatory/noninflammatory lesion counts, treatment success, skin oiliness, treatment-emergent adverse events (TEAEs), and cutaneous safety/tolerability were evaluated. Results: In all participants with oily skin ( n = 793), tazarotene provided greater reductions in inflammatory/noninflammatory lesions ( p < 0.001, both) and greater treatment success rates versus vehicle ( p < 0.01) at week 12. Over two-thirds of polymeric lotion-treated participants had subjective skin oiliness reductions by week 12, with around a third reporting 'low/not' oily skin. Tazarotene TEAE rates were similar to the overall population. Conclusions: Once-daily treatment with tazarotene 0.045% polymeric emulsion lotion may help improve patient-perceived skin oiliness in those with moderate-to-severe acne.